Final testing of vision based AGV navigation module - Loh, Glenn Zhi Kai (2019)
The Unmanned Vehicles (UV) technology advance from military to commercial and industrial usage. Today, a lot of application of the UV is been automated. UV need to able to detect and decide which feature is an obstacle or item of interest while traveling. To provide a safe environment to surrounding near the UV and itself. Not only for the city but in the remote area. The aim of this project was to allow for a situation where human, sun and glare detection software can be portable.